Constitutional and legal basis for ensuring the national security of the Republic of Kazakhstan (Journal of actual problems of jurisprudence, 2021)
This article reveals the current issues of constitutional and legal support of the individual, society and the state. From a legal point of view, security is considered as a set of legal norms, the purpose of which is to protect national interests from existing threats. Special attention is paid to the analysis of the constitutional legislation and the peculiarities of the regulatory regulation of the process of ensuring the national security of the Republic of Kazakhstan. The issues of ensuring the security of the individual, society and the state are among the main ones today. Each state has as its main goal the protection of its sovereignty, the stable development of society, and the decent living of all its participants. Therefore, at the present time, there is a special attention to the problems of national security. This category is the subject of many discussions, political disputes, and theoretical studies. National security can be considered from various points of view: both as the activity of special state bodies to protect national interests, and as the state of protection of the national interests of the country from real and potential threats, and as the creation of conditions for the existence of normal functioning and progressive development of the system itself (society, the state, the people living in it). In our opinion, the modern legislative definition of the concept of national security includes two basic components: security and orientation to progressive development.Keywords: Constitution, national security, national security system, Security Council, national interests.